2019
DOI: 10.1111/and.13400
|View full text |Cite
|
Sign up to set email alerts
|

An additional marker for sperm DNA quality evaluation in spermatozoa of male partners of couples undergoing assisted reproduction technique (IVF/ICSI): Protamine ratio

Abstract: The aim of this study was to evaluate the relationship between the protamine ratio (P1/P2), DNA fragmentation of spermatozoa and protamine deficiency. Patients were grouped into fertile (G1; n = 151) and sub‐fertile (G2; n = 121). DNA fragmentation in spermatozoa was analysed by a TUNEL assay (terminal deoxynucleotidyl transferase‐mediated deoxyuridine triphosphate nick‐end labelling), and the protamination was determined by CMA3 staining, while Western blot was used to measure protamine P1 and P2. While sperm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 87 publications
3
19
0
Order By: Relevance
“…It is not the case. Consistent with our observations, others have reported that there is no correlation between HDS, TUNEL, DFI, CMA3, AB and TB [ 58 , 59 ]. However, some positive correlations have also been reported [ 60 62 ].…”
Section: Discussionsupporting
confidence: 93%
“…It is not the case. Consistent with our observations, others have reported that there is no correlation between HDS, TUNEL, DFI, CMA3, AB and TB [ 58 , 59 ]. However, some positive correlations have also been reported [ 60 62 ].…”
Section: Discussionsupporting
confidence: 93%
“…The relative proportion of protamine quantities P1 and P2 has been proposed in many studies as a biomarker of the maturity and integrity of the sperm chromatin (Amor et al., 2019; Hammadeh et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…From each slide, 500 spermatozoa were evaluated, using a fluorescence microscope (Olympus, Japan). Spermatozoa were classified as follows: bright green spermatozoon (CMA3 positive) had low protamination, and dull green spermatozoa (CMA3 negative) had normal protamination (Amor et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a follow-up study of the same group, a cut-off of 16.8% for DFI has been calculated with high specificity and high positive predictive value (Sharma, Ahmad, Esteves, & Agarwal, 2016 (Yang et al, 2019). In another study, among 272 infertile men who sought for treatment SDF evaluated by TUNEL was found to be negatively correlated with sperm concentration, progressive motility but not correlated with normal morphology (Amor, Shelko, Hamad, Zeyad, & Hammadeh, 2019). Also some studies showed a strong relationship between vitality and SDF (Aghazarian, Huf, Pfluger, & Klatte, 2019.…”
Section: Discussionmentioning
confidence: 99%